Using YouTube to Enhance Elementary Students’ Motivation and Participation in Integrated Science and Social Studies Learning - M Asyraf; Akhmad Habibi; Ugi Nugraha (Papanda Publisher, 2026)
This study aims to analyze the impact of YouTube media on enhancing students’ learning motivation and participation in Science and Social Studies (IPAS) learning at the elementary school level. Employing a Classroom Action Research (CAR) design over two cycles—each consisting of planning, action, observation, and reflection—the study involved 16 fifth-grade students from Izzatul Islam Elementary School, Muaro Jambi Regency. Data were collected using observation sheets, learning motivation questionnaires, and field notes, and analyzed through descriptive quantitative and qualitative techniques. The results showed improvements of 27% in learning motivation and 31% in active participation. Descriptive statistical analysis indicated that these increases were meaningful, and further significance testing using the paired-sample t-test confirmed that the improvements in both motivation and participation were statistically significant (p < 0.05). Students exhibited enhanced attention, curiosity, confidence, and engagement in collaborative discussions after the integration of YouTube-based videos. Overall, the findings suggest that YouTube is an effective digital medium for strengthening students’ affective and social learning aspects while promoting active engagement in the context of digital-era education.